Application of the Problem-Based Learning Model Problem Based Learning To Improve Science Learning Results For Class Iii Students of UPT SDN 190 Barru - Kasy Azzahra, Nur Maghfira; Asmi, Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to improve the learning outcomes of Science and Social Studies (IPAS) among third-grade students at UPT SDN 190 Barru through the application of the Problem Based Learning (PBL) model. The research employed a Classroom Action Research (CAR) methodology, conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through observation and evaluation tests. The results showed significant improvement in students' learning outcomes. In the first cycle, only 25% of students achieved the minimum mastery criterion (KKM) of 70, with an average score of 65.75. However, after implementing improvements in the second cycle, the percentage of students achieving the KKM increased to 80%, with an average score of 79.5. These findings indicate that the PBL model effectively enhances student engagement and learning outcomes in IPAS. The study concludes that PBL is an innovative and effective teaching approach for improving academic performance and developing critical thinking skills among primary school students.